92 views

Uploaded by RickyRefandi

18681858 Math o Level Solution of Quadratic Equation

- Errata digital signal processing prokis manolakis
- 3.3.1 5Yr Integrated M Sc Program Course Structure Syllabus 2015-16 01052015
- AP PGECET Electrical Engg Syllabus and Exam Pattern
- cseSyl0910
- Large Deflection Analysis of Laminated Composite Plates
- Bezier Type Curves
- Numerical Method - Bisection
- Claudia
- 4E AM Term 3 Common Test (2011)
- STPM Trials 2009 Math T Paper 1 (SMI Ipoh)
- Solving Higher Order ODE
- EN1201 Introductory Mathematics V2
- 1.Quanti Preparation_bank Po,Ssc,Sbi Po,Ao Aao,Rbi p1
- Modeling and Analysis of Dynami - Unknown
- equals lesson plan template
- leph2ps
- Heat Transfer Ch3-2D Conduction
- 12-Maths-NcertSolutions-chapter-9-4.pdf
- Van Der Waals' Equation Using Newton Raphson
- Solution_Nonlinear_Hyperbolic_DE_by_Finite_Differences.pdf

You are on page 1of 39

SOLUTION OF

QUADRATIC EQUATION

EXERCISE 1A

Q.1 Solve the following quadratic equations by factorisation:

(a) x2 5x = 0

Solution:

x2 5x = 0

Take x as common

x(x 5) = 0

Either

x=0

or

x5=0

x=5

So, x = 0 or x = 5

(b) 4x2 = 7x

Solution:

4x2 = 7x

4x2 7x = 0

Take x as common

x(4x 1) = 0

Either

x=0

or

4x 7 = 0

7

x=

4

3

4

3

So, x = 0, or x = 1

4

2

(c) 6t = t(6 4)

Solution:

x=1

6t2 = t(t 4)

6t2 t(t 4)

6t2 t2 + 4t = 0

5t2 + 4t = 0

t(5t + 4) = 0

Either

t=0

or

5t + 4 = 0

4

t=

5

So, t = 0, or to

4

5

Solution:

5y2

5y2

5y2

y(4y 3)

=

=

y(y + 3)

y2 + 3y

y2 3y = 0

0

Either

y=0

or

4y 3 = 0

3

y=

4

So, y =

0 or y =

3

4

(e) a2 + 9a = 0

Solution:

a2 + 9a = 0

a(a+9) = 0

Either

a=0

or

a+9=0

a=9

So, a = 0 or 9

(f) 3h = h(5 2h)

Solution:

3h2 = h(5 2h)

3h2 (5 2h) = 0

3h2 + 2h2 5h = 0

5h2 5h = 0

5h(h 1) = 0

Either

h=0

or

h1=0

h=1

So, h = 0 or 1

2

(g) x 2x + 1 = 0

Solution:

x2 2x + 1 = 0

x2 x x + 1 = 0

x(x 1) 1 (x 1) = 0

(x 1)2 = 0

Either

x1=0

x=1

or

2

x1=0

x=1

So, x = 1, 1

(h) 7a + a2 18 = 0

Solution:

7a + a2 18 = 0

Re-arranging

a2 + 7a 18 = 0

a2 + 9a 2a 18 = 0

a(a+9) 2(a+9) = 0

(a+9) (a2) = 0

Either

a+9=0

a = 9

or

a2=0

a=2

So, a = 9 or a = 2

(i)

2x2 + 5z 3 = 0

Solution:

2z2 + 5z 3 = 0

2z2 + 6z z 3 = 0

2z(z+3) 1(z3) = 0

(z+3) (2z1) = 0

Either

z+3=0

z=3

or

2z 1 = 0

1

z=

2

1

So, z = 3 or z

=

2

(j) c2 + 2c = 35

Solution:

c2 + 2c = 35

c2 + 2c 35 = 0

c2 + 7c 5c 35 = 0

c(c+7) 5(c7) = 0

(c+7) (c5) = 0

Either

c+7=0

c=7

or

c5=0

c=5

So, c = 7 or c = 5

(k) 8p 16 p2 = 0

8p 16 p2 = 0

Re-arranging

p2 8pr + 16 = 0

p2 4p 4p + 16 = 0

p(p4) (p4) = 0

Either

p4=0

p=4

or

p4=0

p=4

So, p = 4 or 4

(l)

4 3b b2 = 0

Solution:

4 3b b2 = 0

b3 + 3b 4 = 0

b2 + 4b b 4 = 0

b(b+4) 1(b+4) = 0

(b+4) (b1) = 0

Either

b+4=0

b=4

or

b1=0

b=1

So, b = 4 or b = 1

(m) 12 a a2 = 0

12 a a2 = 0

a2 + a 12 = 0

a2 + 4a 3a 12 = 0

a(a+4) 3(a+4) = 0

(a+4)(a3) = 0

Either

a+4=0

a=4

or

a3=0

a=3

So, a = 4, or a = 3

2

(n) 10t t = 2

Solution:

10t2 t = 2

10t2 t 2 = 0

10t2 5t + 4t 2 = 0

5t(2t1) +2(2t1) = 0

(2t1)(5t+2) = 0

Either

2t 1 = 0

1

t=

2

or

5t + 2 = 0

2

t=

5

So, t =

1

or

2

2

5

(o) y2 22y + 96 = 0

Solution:

y2 22y + 96 = 0

y2 16y 6y + 96 = 0

y(y16) 6(y16) = 0

(y16) (y6) = 0

Either

y 16 = 0

y = 16

or

y6=0

y=6

So, y = 16 or y = 6

2

(p) 12a 16a 35 = 0

12a2 16a 35 = 0

12a2 30a + 14a 35 = 0

6a(2a5) +7(2a5) = 0

(2a 5) (6a + 7) = b

Either

2a 5 = 0

1

a=2

2

or

6a + 7 = 0

6a = 7

7

a=

6

a = 1

1

6

1

1

or a = 1

2

6

2

(q) 15x + 4x 35 = 0

Solution:

15x2 + 4x 35 = 0

15x2 + 25x 21x 35 = 0

5x(3x+5) 7(3x+5) = 0

(3x+5) (5x7) = 0

Either

3x + 5 = 0

5

x=

3

2

x = 1

3

or

5x 7 = 0

7

x=

5

2

x=1

5

2

2

So, x = 1 or a = 1

3

5

2

(r) 15x + 4x 35 = 0

Solution:

28x2 85x + 63 = 0

28x2 36x 49x + 63 = 0

4x(7x9) 7(7x9) = 0

(7x9) (4x7) = 0

Either

7x 9 = 0, 7x = 9

So, a = 2

9

7

2

x=1

7

x=

or

4x 7 = 0, 4x = 7

7

x=

4

3

x=1

4

2

3

So, x = 1 or x = 1

7

4

2

(s) 56x 159x + 108 = 0

Solution:

56x2 159x + 108 = 0

56x2 96x 63x + 108 = 0

8x(7x12) 9(7x12) = 0

(7x12) (8x9) = 0

Either

7x 12 = 0 7x = 12

12

x=

7

5

x=1

7

or

8x 9 = 0, 8x = 9

9

x=

8

1

x=1

8

5

1

So, x = 1 or x = 1

7

8

2

(t) 39x = 131x 44 = 0

10

Solution:

39x2 + 131x 44 = 0

39x2 + 143x 12x 44 = 0

13(3x11) 4(3x11) = 0

Either

3x 11 = 0 3x = 11

2

x=3

3

or

13x 4 = 0 13x = 4

4

x=

13

1

So, x = 3 or x = 4 13

2

(u) 76x 96x2 15 = 0

Solution:

76x 96x2 15 = 0

96x2 76x + 15 = 0

96x2 40x 36x + 15 = 0

8x(12x5) 3(12x5) = 0

(12x5) (8x3) = 0

Either

12x 5 = 0

5

x=

12

or

8x 3 = 0

3

x=

8

5

3

So, x =

or

12

8

Q. Form a quadratic equation in x with the giver roots for

each of the following:

(a) 2, 3

Solution:

Given roots are

x = 2 and x = 3

x2=0

x3=0

(x 2) (x 3) = 0

2

x 2x 3x + 6 = 0

x2 5x + 6 = 0

(b) 3, 4

Solution:

Given roots are

x = 3 and x = 4

x3 = 0

x+4 = 0

(x3) (x+4) = 0

2

x 3x + 4x 12 = 0

x2 + x 12 = 0

(c) 5, 0

Solution:

Given roots are

x = 5 and x = 0

x+5=0

x6=0

(x + 5) (x 6) = 0

x2 x 30 = 0

1

(d) 5,

2

Solution:

1

x = 5 and

x=

2

x5=0

2x 1 = 0

11

12

(x 5) (2x 1) = 0

2x2 x 10x + 5 = 0

2x2 11x + 5 = 0

2 4

,

3 5

Solution:

Given roots are

2

4

x=

and x =

3

5

3x 2 = 0

5x + 4 = 0

(3x 2) (5x + 4) = 0

15x2 + 12x 10x 8 = 0

15x2 + 2x 8 = 0

7 5

(f)

,

8 8

Solution:

Given roots are

7

5

x=

and

x=

8

6

8x = 7

6x = 5

8x + 7 = 0

6x 5 = 0

So our required equation is

(8x + 7) (6x 5) = 0

2

48x 40x + 42x 35 = 0

48x2 + 2x 35 = 0

1 3

(g) 2 , 1

2 4

Solution:

Given factors

1

3

x = 2

and

x=1

2

4

(e)

5

7

, 2xn = 5

x=

x,n = 7

2

4

2x + 5 = 0

4x 7 = 0

So our required equation is

(2x + 5) (4x + 7) = 0

2

8x + 14x + 20x + 35 = 0

8x2 + 34x + 35 = 0

1 2

(h) 1 ,

2 3

Solution:

Given factors

1

2

x = 1

and x = , 3n = 2

2

3

3

x=

, 2n = 3

3x = 2

2

2x + 3 = 0

3x 2 = 0

So our required equation is

(2x + 3) (3x 2) = 0

6x2 4x + 9x 6 = 0

6x2 + 5x 6 = 0

4 4

(i)

,

7 7

Solution:

Given the factors

4

4

x=

and

x=

7

7

7x + 4 = 0

7x + 4 = 0

So our required equation is,

(7x + 4) (7x + 4) = 0

49x2 + 28x + 28x + 16 = 0

49x2 + 56x + 16 = 0

x=

13

14

EXERCISE No. 1B

Q.1. Solve the following equations, giving your answers correct

to 2 decimal places where necessary.

(a) (x + 1)2 = 9

Solution:

(x + 1) = 9

Taking the square root of each side.

Either,

x+1 =3

x =2

or

x+1 =3

x =4

2

(b) (2x + 1) = 16

Solution:

(2x + 1) = 16

Taking the square root of each side.

Either,

2x + 1 = 4

3

x =

2

x = 1.5

or

2x + 1 = 4

5

x =

2

x = 2.5

(c) (3x + 2)2 = 49

Solution:

(3x + 2) = 49

Taking the square root of each side.

Either.

3x + 2 7

15

5

3

x = 1.67

x =

or

3x + 2 = 7

x =3

2

29

3

(d) 2x + =

45

4

Solution:

Taking the square root of each side.

Either,

3

7

2x +

=

4

5

7 3

2x =

5 4

28 15

2x =

20

13

x =

40

x = 0.33

or

3

7

2x +

=

4

5

7

3

2x =

5

4

28 15

2x =

20

43

x =

40

x = 1.08

(e) (5x 4) = 81

Solution:

2

(5x 4) = 81

16

Either.

5x 4 = 9

13

x =

5

x = 2.60

or

5x 4 = 9

5

x =

5

x =1

25

(f) (3x +7)2 =

49

Solution:

Taking square root of each side.

Either,

5

3x + 7 =

7

5

3x =

7

7

5 49

3x =

7

44

x =

21

x = 2.10

or

5

3x + 7 =

7

5

3x =

7

7

5 59

3x =

7

17

54

21

x = 2.57

x =

(g)

(x-4)2 = 17

(x 4)2

Taking square rot of each side.

Either,

x5

x

or

x4

x

2

(h) (x + 3) = 11

Solution:

(x + 3y)

Taking square root of each side.

Either,

x+3

x

or

x+3

x

2

(i)

(2x 3) = 23

Solution:

(2x 3)

Taking square root of each side.

Either,

2x 3

x

or

2x 3

x

2

(j) (3x +2) = 43

Solution:

=7

= 4.12

= 8.12

= 4.12

= 0.12

= 11

= 3.32

= 0.32

= 3.32

= 6.32

= 23

= 4.80

= 3.90

= 4.80

= 0.90

18

(3x + 2) = 43

Taking square root of each side.

Either,

3x + 2 = 6.65

x = 1.32

or

3x + 2 = 6.56

x = 2.85

2

(k) (5x 7) = 74

Solution:

(5x 7) = 74

Taking square root of each side.

Either,

5x 7 = 8.6

x = 3.12

or

5x 7 = 8.6

x = 0.32

2

(l)

(3 + 7x) = 65

Solution:

(3 + 7x)2 = 65

Taking square root of each side.

Either,

3 + 7x = 8.06

7x = 8.06

3

7x = 5.06

x = 0.72

or

3 + 7x = 8.06

7x = 8.06 3

7x = 11.06

x = 1.38

Q.2 What number must be added to each of the following

expressions to obtain a perfect square?

19

(a) x2 + 7x

Solution:

Given expression is x2 + 7x

The coefficient of x is 7.

So square of half of will be added both side.

7

x + 7x +

2

= x +

2

7

must be added

2

2

(b) x 3x

Solution:

Given expression is x2 3x

The coefficient of x is 3

So square of half of 3 will be added both side.

3

x2 3x +

= x

2

must be added

2

7

(c) x2 + x

2

Solution:

7

Given expression is x2 + x

2

7

The coefficient of x is

2

So square of half of 7 2 must be added.

2

7

7

x + x+

2

2

2

2

49

7

must be added.

=

16

2

= x +

2

20

(d) x2 1.8x

Solution:

Given expression is x2 1.8x

The coefficient of x is 1.8 =

9

5

x2

9

9

x+

5

10

= x

10

81

must be added.

100

(e) a2 + 2.4a

Solution:

Given the expression is a2 + 2.4n

12

The coefficient of a is 2.4 =

5

12

So square of half of

will be added both side.

5

x2 +

2

12

6

a+

5

5

= a +

5

36

must be added.

25

2

(f) c2 + 4 c

3

Solution:

2

3

14

.

3

So square of half of 14 3 will be added both side.

The coefficient of c is

c2 +

2

14

7

c+

3

3

= c +

3

21

2

49

7

must be added.

=

9

3

4

(g) y2 + y

5

Solution:

4

Given the express in is y2 = y

5

4

The coefficient of y is .

5

So squared half of 4 5 will be added both side.

y2 +

2

y

2

y+

5

5

= y +

5

4

must be added.

25

1

(h) v2 3 v

2

Solution:

Given expression is v2 3

The coefficient of v is

p2

1

v

2

7

2

2

7

7

v+

2

4

= v2

4

2

49

7

must be added.

or

16

4

(i)

b2 10kb

Solution:

Given the expression is b2 10kb

10k

= 5k.

2

= (b 5k)2

b2 10kb + (5k)2

22

(j) g2 5kg

Solution:

Given expression is g2 5kg

The coefficient of g is 5k. Half of this is

5k

g2 5kg +

5k

.

2

5k

= y

2

25k 2

must be added.

4

(k) h2 + 3mh

Solution:

Given expression is h2 +3mh

3m

h2 + 3mh +

3m

.

2

3m

= h +

9m 2

must be added.

4

1

(l)

k2 1 k

3

Solution:

1

Given expression is k2 1 k.

3

4

2

The coefficient of k is

. Half of this is

3

3

4 2 2

k

+

3 3

2

4

must be added.

9

(m) d2 + 10xd

Solution:

= k

3

23

The coefficient of d is 10x. Half of this is 5x.

D2 + 10xd + (5x)2 = (d + 5x)2

(n) h2 5xk

Solution:

Given expression is k2 5xk

This is a quadratic expression in k.

5x

The coefficient of k is 5x. Half of this is

.

2

5x

k 5xk +

2

2

5x

= x

2

25x 2

must be added.

4

(o) m2 5n2m

Solution:

Given expression is m2 5n2m

This is a quadratic expression in m.

5n 2

m 5n m +

2

5 2

n.

2

5n 2

= m

25n 4

must be added.

4

EXERCISE NO.1C

Q.

possible or by completing the square. If the answers involve

decimal places, give them correct to 2 decimal places. If an

equation has no real roots, indicate that this is so.

(a) x2 + 2x + 3 = 0

Solution:

x2 + 2xz + 3 = 0

24

x2 + 2x = 3

x2 + 2x + (1)2 = 3 + (1)2

(x + 1)2 = 2

Either,

2

x+1 =+

or

x+1 = 2

Hence, roots of x + 2x + 3 = 0 are complex.

(b) 5x2 4x 2 = 0

Solution:

5x2 4x 2 = 0

4

2

x2 x

=0

5

5

4

2

x2 x =

5

5

2

x2

2

4

2

x+

5

5

x

5

2 2 2

+

5 5

14

15

Either,

x

2

5

14

25

x 0.4 = 0.75

x = 1.15

or

x

2

5

14

25

x 0.4 = 0.75

x = 0.35

(c) 2x2 + 7x + 2 = 0

Solution:

2x2 + 7x + 2 = 0

25

7

x+1 =0

2

7

x2 + x = 1

2

7

x2 + x = 1

2

x2 +

2

7

7

x + x+

2

4

2

x +

3

7

= 1 +

4

33

16

Either,

7

33

=

4

16

x + 1.75 = 1.44

x = 0.31

x+

or

x+

7

4

33

16

x + 1.75 = 1.44

x = 3.19

(d) 4x2 = 5x 21

Solution:

4x2 = 5x 21

5

x

x2 = x

4

4

5

21

x2 x =

4

4

2

5

5

x x+

4

8

2

x

8

21 5 2

=

+

4

8

311

64

26

Either,

x

5

8

=+

311

64

5

8

311

64

or

(c) 2x2 + 5x 3 = 0

Solution:

2x2 + 5x 3 = 0

5

3

x2 + x

=0

2

2

5

3

x2 + x =

2

2

x2 +

5

4

x +

4

5

x+

2

3 5 2

+

2 4

49

16

Either,

x+

5

4

7

4

2

x =

4

1

x =

2

x+

5

4

or

(f)

3x2 + 8x + 2 = 0

7

4

12

x =

4

x =3

=

27

Solution:

3x2 + 8x + 2 = 0

8

2

x2 + x +

=0

3

3

8

2

x2 + x =

3

3

x2 +

4

3

x +

3

8

x+

3

2

2

4

+

3

3

10

9

Either,

x+

4

3

10

9

x = 1.054 1.33

x = 0.28

or

x+

4

3

10

9

x = 1.054 1.33

x = 2:39

(g) 7x2 28x + 15 = 0

Solution:

7x2 28x + 15 = 0

15

x2 4x +

=0

7

15

x2 4x =

7

15

x2 4x + (2)2 =

+ (2)2

7

17

(x 2)2 =

7

Either,

28

13

7

x2 =

x 2 = 1.36

x 2 = 3.36

or

13

7

x2 =

x 2 = 1.36

x = 0.64

(h) 5x2 + 12x + 3 = 0

Solution:

5x2 + 12x + 3 = 0

12

3

x2 +

x+

=0

5

5

12

3

x2 +

x =

5

5

x2 +

2

12

6

x+

5

5

x +

5

3 6 2

+

5

5

21

25

Either,

x+

6

5

21

25

x + 1.10 = 0.918

x = 0.918 1.10

x = 2.02

(i)

2x2 + 3x 4 = 0

Solution:

2x2 + 3x 4 = 0

3

x2 + x 2 = 0

2

29

x2 +

x2 +

3

x =2

2

3

4

x +

4

3

x+

2

3

=2+

4

=

41

16

Either,

3

41

=

4

16

x + 0.75 = 1.6

x = 0.85

x+

or

x+

3

4

41

16

x + 0.75 = 1.6

x = 2.35

(j) x2 12x + 36 = 0

Solution:

x2 12x + 36

(x)2 2(x) (6) + (6)2

(x6)2

(x6) (x6)

x

So, x may be 6 repeated.

(k) 5x2 + 30x 18 = 0

Solution:

5x2 + 30x 18

18

x2 + 6x

5

=0

=0

=0

=0

=6

=0

=0

x2 + 6x =

18

5

or 6

30

18

+ (3)2

5

63

=

5

x2 + 6x + (3)2 =

(x+3)2

Either,

63

5

x + 3 = 3.55

x = 0.55

x+3 =

or

x+3 =

63

5

x + 3 = 3.55

x = 6.55

(l)

3x2 4x + 7 = 0

Solution:

3x2 4x + 7 = 0

4

4

x2 x +

=0

3

3

4

7

x2 x =

3

4

2 2 2

(x)2 2(x) +

3 3

2

x

3

x

3

7 2 2

+

3 3

7

4

+

3

9

21 + 4

9

17

9

x

3

31

2

3

17

9

(m) 3x2 + x 2 = 0

Solution:

3x2 + x 2 = 0

x

2

x2 +

=0

3

3

x

2

x2 +

=

3

3

x2 +

2

x

1

+

3

6

x +

6

2 1 2

+

3 6

25

36

Either,

x+

1

6

5

6

4

x =

6

2

x =

3

x+

1

6

or

5

6

6

x =

6

x = 1

=

(n) x2 11x 26 = 0

Solution:

x2 11x 26 = 0

x2 11x = 26

32

11

x2 11x +

2

11

x

2

11

= 26 +

2

225

4

Either,

x

11

2

15

2

26

x =

2

x = 13

11

2

or

15

2

4

x =

2

x =2

=

(o) 3x2 + 5x 2 = 0

Solution:

3x2 + 5x 2 = 0

5

2

x2 + x

=0

3

3

5

2

x2 + x =

3

3

x2 +

5

6

x +

6

5

x+

3

2 5 2

+

3 6

49

36

Either,

x+

5

6

7

6

2

x =

6

=

33

x =

1

3

or

x+

7

6

12

x =

6

x =2

5

6

(p) 2x 3x2 4 = 0

Solution:

2x 2x2 4

3x2 2x + 4

2

4

x2 x +

3

3

2

x2 x

3

1 1

(x)2 2(x) +

3 3

=0

=0

=0

=

4

3

4 1 2

+

3 3

4

1

+

3

9

12 + 1

9

20

9

x

3

x

3

x

3

x

1

3

(q) x2 7x 30 = 0

Solution:

x2 7x 30 = 0

20

9

34

x2 7x = 20

7

x2 7x +

2

4

2

7

= 30 +

2

=

169

4

Either,

x

7

2

13

2

20

x =

2

x = 10

7

2

or

13

2

6

x =

2

x =3

Solution:

(2x + 3) (x 2) x (x + 1)

(2x2 x 6) (x2 + x)

x2 2x 6

x2 2x

x2 2x + (1)2

(x 1)2

Either,

=0

=0

=0

=6

= 6 + (1)2

=7

x1 =

1 = 2.65

x = 3.65

or

x =

x 1 = 2.65

35

x = 1.65

(s) x 6x 16 = 0

Solution:

2

x2 6x 16

x2 6x

x2 6x + (3)2

(x 3)2

=0

= 16

= 16 + (3)2

= 25

Either,

x3 =5

x =8

or

x3 =5

x =2

(t)

2x2 x 3

1

=0

2

Solution:

1

2

7

2x2 x

2

x

7

x2

2

2

x

x2

2

2x2 x 3

x2

2

x

1

+

2

4

x

4

=0

=0

=0

=

7

4

7 1 2

+

4 4

29

16

Either,

x

1

4

29

16

x 0.25 = 1.35

36

x = 1.60

or

x

1

4

29

16

x 0.25 = 1.35

x = 1.10

(u) x2 16x 10 = 0

Solution:

x2 16x 10

x2 16x

x2 16x + (8)2

(x 8)2

=0

= 10

= 10 + (8)2

= 74

Either,

x8 =

74

x 8 = 8.60

x = 16.60

or

x8 =

74

x 8 = 8.60

x = 0.60

2

(v) (2x + 1) (5x 4) (3x 2) = 0

Solution:

(2x + 1) (5x 4) (3x 2)2 = 0

(10x2 3x 4) (9x2 12x + 4) = 0

x2 + 9x 8 = 0

x2 + 9x = 8

Either,

9

x2 + 9x +

2

x +

2

9

=8+

2

=

113

4

37

9

113

=

2

4

x + 4.5 = 5.32

x = 0.82

x+

or

x+

9

2

113

4

x + 4.5 = 5.32

x = 9.82

(w) x2 2x 5 = 0

Solution:

x2 2x 5

x2 2x

x2 2x + (1)2

(x 1)2

=0

=5

= 5 +(1)2

=6

Either,

x1 =

x 1 = 2.45

x =3.45

or

x1 =

x 1 = 2.45

x = 1.45

(x) 5x2 8x 30 = 0

Solution:

5x2 8x 30 = 0

x

x2

6 =0

5

x

x2 x = 6

5

3

x

4

x

+

5

5

2

4

= 6+

5

38

x

5

166

25

Either,

x

4

5

166

25

x 0.8 = 2.58

x = 3.38

or

x

4

5

166

25

x 0.8 = 2.58

x = 1.78

(y) 4x(3x 1) 2 = (2x 1) (5x + 1)

Solution:

4x(3x 1) 2 = (2x 1) (5x + 1)

12x2 4x 2 = 10x2 3x 1

12x2 4x 2 + 3x + 1 = 0

2x2 x 1 = 0

x

1

x2

=0

2

2

x

1

x2

=

2

2

x2

2

x

1

+

2

4

x

4

1 1 2

+

2 4

9

16

Either,

x

1

4

3

4

4

x =

4

x =1

=

39

or

x

3

4

2

x =

4

1

x =

2

1

4

Solution:

5x2 16x + 2 = 0

16

2

x2

x+

=0

5

5

16

2

x2

x =

5

5

2

16

8

x

x+

5

5

2

x

5

2

2

8

=

+

5

5

54

25

Either,

x

8

5

54

25

x 1.6 = 1.47

x = 3.07

or

x

8

5

54

25

x 1.6 = 1.47

x = 0.13

__________

- Errata digital signal processing prokis manolakisUploaded byAjinkya Kale
- 3.3.1 5Yr Integrated M Sc Program Course Structure Syllabus 2015-16 01052015Uploaded byPrity Gupta
- AP PGECET Electrical Engg Syllabus and Exam PatternUploaded bygayathri
- cseSyl0910Uploaded bygenius_vikash2405
- Large Deflection Analysis of Laminated Composite PlatesUploaded byHakan Tanriover
- Bezier Type CurvesUploaded byxulescuhulescu
- Numerical Method - BisectionUploaded byAmeq Azaulmay
- ClaudiaUploaded byemanueluntesu
- 4E AM Term 3 Common Test (2011)Uploaded byvr72here3168
- Solving Higher Order ODEUploaded byOlivier Ruatta
- EN1201 Introductory Mathematics V2Uploaded byChathura Kumara
- 1.Quanti Preparation_bank Po,Ssc,Sbi Po,Ao Aao,Rbi p1Uploaded bydsdas
- STPM Trials 2009 Math T Paper 1 (SMI Ipoh)Uploaded byHaRry Chg
- Modeling and Analysis of Dynami - UnknownUploaded byPaulCampues
- equals lesson plan templateUploaded byapi-291355677
- leph2psUploaded byMurali
- Heat Transfer Ch3-2D ConductionUploaded byDinesh Bala Krishnan
- 12-Maths-NcertSolutions-chapter-9-4.pdfUploaded byKaran Pratap
- Van Der Waals' Equation Using Newton RaphsonUploaded bykenn veloso
- Solution_Nonlinear_Hyperbolic_DE_by_Finite_Differences.pdfUploaded byjhonmichael0022
- Day 1Uploaded byjoe_ochiltree
- edu 537 lesson planUploaded byapi-279892938
- Linear Equation in One VariableUploaded byDanilo de Mesa
- Finite Diferences for the Wave EquationUploaded byPhilip Kent
- 2011 MSM DIfferential Equation (Solutions)Uploaded bylimkewchong
- Multi-Well Allocation (MWA) ExercisesUploaded byQuy Tran Xuan
- algebra 1 course descriptionUploaded byapi-328719919
- ACT MathUploaded bykingkola36
- Moitsheki Raseelo J Makinde Oluwole D Eng 2010Uploaded byIsmatov Tolib
- Differential Equations - Vibrating StringUploaded bymanish

- Quadratic Equations, algebra revision notes from GCSE Maths TutorUploaded bygcsemathstutor
- 18681858 Math o Level Solution of Quadratic EquationUploaded byRickyRefandi
- Quadratic Equation (2)Uploaded byrajesh_iitg
- Quadratic Equations and FunctionsUploaded byapi-3709402
- Chapter 13 Meiosis and Sexual LifecycleUploaded byRickyRefandi
- characteristicsoflivingthings-organismaUploaded byRickyRefandi
- Bacteria2Uploaded byananth
- Nature of the SolutionsUploaded byRickyRefandi
- Have Been Explained That the Emergency Resolution Determining the Set of Quadratic Equations by Quadratic FormulaUploaded byRickyRefandi
- A Warning Against Ideological Fanaticism(Zein)Uploaded byRickyRefandi
- NO 3ana Oke SiipUploaded byRickyRefandi
- Quadratic EquationUploaded byMalaysiaBoleh
- drama SECUploaded byRickyRefandi

- Mold & Mold MakingUploaded byMohd Syafiq Ab Manaf
- REV12 Data SheetUploaded bySheilapb
- Avr - Unitrol 1000-15 eUploaded bysquare17.gopi
- Chem Project HiteshUploaded bySahil Sharma
- MATLAB Simulation of a Variable Speed Controller for a Three Phase Induction MotorUploaded bySanila Cm
- Microsoft Word - STOICHIOMETRY-ASSIGNMENT - 1.pdfUploaded byggk2013
- Matlab AssignmentUploaded byAsad Zahid
- Resonant Inductive Coupling WPTUploaded byABHIJIT CHANDRA
- CFD ANALYSIS OF HEAT TRANSFER IN A HELICAL COIL HEAT EXCHANGER USING FLUENTUploaded byAttique Javaid
- Lesson Plan RSBIUploaded byaries triwidajati
- Cam Design Chap 01Uploaded byzinmgoo
- Power Sys MagazineUploaded byTristan Cabatac
- Hea2000 Specification E-005c 040413 Fpds r1Uploaded byDiggy Breiling
- 08 Archimedes InstructionsUploaded byAfini Exo K
- Evaluation of High Power Energy Storage Devices for Use in Compact Pulsed Power SystemsUploaded bybijushresth
- Inverter KEBUploaded byDomenico Leuzzi
- High Dp Orifice FlowUploaded bytibitomic
- ssc-jen-paper-1st.pdfUploaded byamrit
- Rotary PumpUploaded bysushant_jhawer
- Libro Non Lineal Phenomena in BiologyUploaded byCarlos Hernandez Montes
- Sandblaster ManualUploaded bygmelloy
- Aristotles PhysicsUploaded bygastrobar
- Servo Motor - engineersgarage.docxUploaded byanggota
- final beam technical reportUploaded byapi-302577590
- Automobile Engineering - Engine Cooling SystemsUploaded byAhmed Zawad Shovon
- Classical Algebraic GeometryUploaded byalin444444
- En-msds Bonderite C-ic Alutech 30kg(Ex) (1900202) 04.11.2014Uploaded byChutha
- 219_ftp.pdfUploaded byGary Kiel Palacios Espinoza
- Nanofluids and Its Thermal Applications (122)Uploaded byMandeep Singh
- MS 1462-2-2-2010 (CONFIRMED 2015) SOILUploaded byGan Chin Phang